THU0169 TRAF3IP2 gene polymorphisms are associated with susceptibility to systemic lupus erythematosus. (23rd January 2014) - Perricone, C.; Di Fusco, D.; Ciccacci, C.; Ceccarelli, F.; Cipriano, E.; Spinelli, F.R.; Borgiani, P.; Valesini, G.; Conti, F.
Abstract : Background: Systemic lupus erythematosus (SLE) is a multifactorial autoimmune disease of unknown etiology. Only few genes have been associated with disease susceptibility exerting a strong risk effect. TRAF3IP2 gene has been recently associated with susceptibility to psoriatic arthritis and psoriasis. This gene encodes for Act1, a signalling adaptor involved in the regulation of adaptive immunity acting as a negative regulator of humoral immunity and as a positive signalling adaptor in IL-17-mediated cellular immune responses. These evidences suggest that TRAF3IP2 could be implicated in SLE pathogenesis. Objectives: The aims of this study are to identify additional genes contributing to SLE susceptibility, and to replicate the association between STAT4, IL-10, IL-23R genes with SLE. Methods: Two-hundred fourty consecutive SLE patients were enrolled. Study protocol included complete physical examination, the clinical and laboratory data were collected in a standardized electronically-filled form including demographics, past medical history, co-morbidities, previous and concomitant treatments. Laboratory analysis included anti-nuclear, anti-double-stranded DNA, anti-cardiolipin, anti-β2-glycoprotein I antibodies (assessed with indirect immunofluorescence or ELISA according to previously described methods). Three hundred age- and ethnicity-matched healthy subjects served as controls. Genotype analysis was performed by allelic discrimination assays using TaqMan technology with specific allelic probes (Applied Biosystems, Foster City, CA, USA) and ABI PRISM. Hardy-Weinberg equilibrium (HWE) for each SNP, as well as differences in allelic and genotypic frequencies between cases and control or among phenotypic groups were evaluated by Pearson χ 2 test. Statistic analyses were performed by SPSS software. Results: All genotypes were in HWE. TRAF3IP2 (rs33980500, rs13190932 and rs13193677), IL-23R (rs11209026, rs7517847 and rs11805303), IL-10 (rs3024505, and rs1800872) and STAT4 (rs7574865) polymorphisms were analyzed (in both cases and controls). We confirm that STAT4 rs7574865 has a strong association with susceptibility to SLE (P=0.00016, OR=2) as well as IL-10 rs3024505 (P=0.02, OR=1.52) and IL-10 rs1800872 (P=0.027, OR=0.68). Moreover, TRAF3IP2 rs33980500 and rs13193677 resulted associated with susceptibility to SLE (P=0.023, OR=1.7, and P=0.048, OR=1.72, respectively). Data were analyzed for evidence of significant genotype-phenotype associations. TRAF3IP2 rs13190932 was associated with the presence of malar rash (P=0.041, OR=2.14). All three TRAF3IP2 SNPs resulted associated with the development of pericarditis: in particular rs33980500 showed the strongest association (P=0.003, OR 2.83). No other associations were found. Conclusions: Our study provides new insights into the pathophysiology of SLE, highlighting TRAF3IP2 as a novel susceptibility gene. This gene may also affect disease phenotype. Indeed, interestingly, the previously described association with psoriasis suggests that this protein acts in key pathogenic pathways occurring in the skin. Disclosure of Interest: None Declared